The role of ncRNAs and exosomes in the development and progression of endometrial cancer - Niebora, Julia; Woźniak, Sławomir; Domagała, Dominika; Data, Krzysztof; Farzaneh, Maryam; Zehtabi, Mojtaba; Dari, Mahrokh Abouali Gale; Pour, Fatemeh Khojasteh; Bryja, Artur; Kulus, Magdalena; Mozdziak, Paul; Dzięgiel, Piotr; et al. (Frontiers in Oncology, 2024)
Endometrial cancer (EC) is one of the most common gynecologic cancers. In recent years, research has focused on the genetic characteristics of the tumors to detail their prognosis and tailor therapy. In the case of EC, genetic mutations have been shown to underlie their formation. It is very important to know the mechanisms of EC formation related to mutations induced by estrogen, among other things. Noncoding RNAs (ncRNAs), composed of nucleotide transcripts with very low protein-coding capacity, are proving to be important. Their expression patterns in many malignancies can inhibit tumor formation and progression. They also regulate protein coding at the epigenetic, transcriptional, and posttranscriptional levels. MicroRNAs (miRNAs), several varieties of which are associated with normal endometrium as well as its tumor, also play a particularly important role in gene expression. MiRNAs and long noncoding RNAs (lncRNAs) affect many pathways in EC tissues and play important roles in cancer development, invasion, and metastasis, as well as resistance to anticancer drugs through mechanisms such as suppression of apoptosis and progression of cancer stem cells. It is also worth noting that miRNAs are highly precise, sensitive, and robust, making them potential markers for diagnosing gynecologic cancers and their progression. Unfortunately, as the incidence of EC increases, treatment becomes challenging and is limited to invasive tools. The prospect of using microRNAs as potential candidates for diagnostic and therapeutic use in EC seems promising. Exosomes are extracellular vesicles that are released from many types of cells, including cancer cells. They contain proteins, DNA, and various types of RNA, such as miRNAs. The noncoding RNA components of exosomes vary widely, depending on the physiology of the tumor tissue and the cells from which they originate. Exosomes contain both DNA and RNA and have communication functions between cells. Exosomal miRNAs mediate communication between EC cells, tumor-associated fibroblasts (CAFs), and tumor-associated macrophages (TAMs) and play a key role in tumor cell proliferation and tumor microenvironment formation. Oncogenes carried by tumor exosomes induce malignant transformation of target cells. During the synthesis of exosomes, various factors, such as genetic and proteomic data are upregulated. Thus, they are considered an interesting therapeutic target for the diagnosis and prognosis of endometrial cancer by analyzing biomarkers contained in exosomes. Expression of miRNAs, particularly miR-15a-5p, was elevated in exosomes derived from the plasma of EC patients. This may suggest the important utility of this biomarker in the diagnosis of EC. In recent years, researchers have become interested in the topic of prognostic markers for EC, as there are still too few identified markers to support the limited treatment of endometrial cancer. Further research into the effects of ncRNAs and exosomes on EC may allow for cancer treatment breakthroughs.